2021
DOI: 10.1111/vco.12769
|View full text |Cite
|
Sign up to set email alerts
|

Familial follicular cell thyroid carcinomas in a large number of Dutch German longhaired pointers

Abstract: Thyroid carcinomas (TCs) originating from follicular cells of the thyroid gland occur in both humans and dogs, and they have highly similar histomorphologic patterns. In dogs, TCs have not been extensively investigated, especially concerning the familial origin of TCs. Here, we report familial thyroid follicular cell carcinomas (FCCs) confirmed by histology in 54 Dutch origin German longhaired pointers. From the pedigree, 45 of 54 histopathologically confirmed cases are closely related to a pair of first-half … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although the inbreeding level in Dutch GLPs is relatively low in comparison to other 11 pointer setter breeds according to the current study, inbreeding level in certain subpopulations of GLPs is high and this probably contributes to the high incidence of follicular cell thyroid carcinoma. (Yu et al, 2021 , 2022 ). To eradicate genetic defects from GLPs, inbreeding control is essential.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the inbreeding level in Dutch GLPs is relatively low in comparison to other 11 pointer setter breeds according to the current study, inbreeding level in certain subpopulations of GLPs is high and this probably contributes to the high incidence of follicular cell thyroid carcinoma. (Yu et al, 2021 , 2022 ). To eradicate genetic defects from GLPs, inbreeding control is essential.…”
Section: Discussionmentioning
confidence: 98%
“…Besides the popularity of GLP in Germany, breeding GLPs is also popular in the Netherlands. The Dutch population of GLP was found to be predisposed to a genetic form of follicular cell thyroid carcinoma (FCC) (Yu et al, 2022 ). Inbreeding analysis based on both pedigree and SNP array genotype data indicated that inbreeding contributed to the high incidence of the genetic FCC in the population (Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We selected 7 GLPs affected by familial FCC from the dataset described previously, and inclusion in this study was approved by the owners [ 1 ]. Tumor tissues and blood samples were collected during the surgery or necropsy.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported familial thyroid follicular cell carcinomas (FCCs) in 54 Dutch German longhaired pointers (GLPs), identified by histological examination and an additional 29 dogs were suspected to be affected based on typical clinical signs [ 1 ]. The familial FCC was heterogeneous with 5 different histological subtypes: follicular thyroid carcinoma (FTC), papillary thyroid carcinoma (PTC), compact thyroid carcinoma (CTC), follicular-compact thyroid carcinoma (FCTC), and carcinosarcoma.…”
Section: Introductionmentioning
confidence: 99%